The World Bank Group A to Z 2016 - World Bank Group (Washington, DC: World Bank, 2015)
Note: Information in this title reflected the institution at the time of publication and may be subject to change... The World Bank Group A to Z provides concise and essential information about the mission, policies, procedures, products, and services of the new World Bank Group.